PENGARUH KARAKTERISTIK PENGANGGARAN, PENERAPAN SISTEM INFORMASI AKUNTANSI DAN AKUNTABILITAS PUBLIK TERHADAP KINERJA MANAJERIAL SATUAN KERJA PERANGKAT DAERAH (Studi Empiris pada Satuan Kerja Perangkat Daerah (SKPD) Kabupaten Batang Hari) - Yulia Istia Ningsih (Universitas Batanghari Jambi, 2017)
This research aims to test the influence of the characteristics of the application of budgeting, accounting information systems, and public accountability against the performance of managerial Work Unit (SKPD) Area Device Batang Hari. The phenomenon in this study is the evaluation of the Governors of the five Day Rod Unit WorkingDevice area (SKPD) because it is not able to achieve the original target of revenue (PAD) Region in the year 2014. The population of this research is the entire FinancialManager Officer Derah Unit Working Device area (SKPD) Batang Hari. Samples prepared in this research as much as 146 by using purposive sampling method. Data collected by way of disseminating a questionnaire. The research of using multiple regression analysis with Statistical Product and Service Solution (SPSS) version 22. The results of this study indicate that simultaneous budget participation variables, clarity of goals to budget, budget feedback, the difficulty of the achievement of objectives, the evaluation of the implementation of the budget, accounting information systems, and public accountability effect on managerial performance. Clarity of goalsto budget, budget feedback, evaluation, budget and public accountability in partialeffect significantly to managerial performance, whereas a variable participation budget, the difficulty of the achievement of the goals, and the application of the systemaccounting information has no effect on performance of significant managerial. The results of this research show that the independent variables the dependent variableimpact of 96.4%.Keywords: managerial performance, budget participation